Comprehensive management of diastasis recti abdominis after childbirth: a literature review - Janiszewska, Michalina; Feja, Ewa; Łuczak, Janusz (Journal of Education, Health and Sport, 2025)
Introduction: Diastasis recti abdominis (DRA) is a frequent postpartum condition characterized by separation of the rectus abdominis muscles along the linea alba. Although often considered benign, it may contribute to trunk instability, low back pain, pelvic floor dysfunction, and body image concerns. Increasing evidence recognizes DRA as both a functional and psychosocial component of postpartum recovery. Methods: This narrative review summarizes latest studies, including randomized trials, observational cohorts, systematic reviews, and expert consensus statements. The analysis focuses on pathophysiology, diagnosis, conservative rehabilitation, pelvic floor integration, and minimally invasive surgery. Results: Evidence supports early, guided exercise programs emphasizing transversus abdominis activation, hypopressive breathing, and pelvic floor co-contraction as effective in reducing inter-rectus distance (IRD) and improving functional stability. Adjunctive modalities such as neuromuscular electrical stimulation, manual therapy, and Kinesio taping may enhance recovery and psychological well-being. For persistent or severe DRA (>3–5 cm) or DRA with midline hernia, minimally invasive repairs such as MIRRAD and retromuscular or endoscopic sublay approaches offer high patient satisfaction, rapid recovery, and low complication rates. Recent classification systems and national consensus statements have improved diagnostic clarity and treatment planning. Conclusions: DRA management requires a multidisciplinary, individualized approach. Early screening, evidence-based physiotherapy, and integration of pelvic floor and psychological support are essential to optimize recovery. Future work should prioritize standardized diagnostic methods, long-term functional outcomes, and the creation of international rehabilitation guidelines.